The Role Of Information Technology In Improving The Efficiency Of Banking Innovations (A Field Study On Public Banks In Lattakia Governorate) - قاسم سامر; ابراهيم أيهم (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aims to study the relationship between information technology (the availability of information technology dimensions, human resources skills, communication networks, databases) and the efficiency of banking innovations in the branches of public Syrian banks in Lattakia Governorate. The efficiency index of banking innovations was calculated by calculating the ratio of the output index to the index the inputs are based on the Global Innovation Index GII model. To achieve this, three main hypotheses were formulated. The researcher used the questionnaire method to collect the data that were analyzed using statistical tests, the most important of which are: One-Sample T. test, Pearson Correlation test, and regression analysis. The researcher reached several results, the most important of which are: There is a good direct relationship between information technology and the input index and the output index, but there is a weak inverse relationship between information technology and the innovation efficiency index, and therefore the resources available in the public banks under study are not invested in order to achieve work efficiency. Banking with regard to providing banking innovations and achieving productivity indicators that ensure the stability of the financial position in the banking market.